Bridging the gap: Perceived behavioral control and social norms as mediators between Islamic education and prayer practice - Hazmar, Al Afif; Larasati , Indah; Nurjayanti, Nurjayanti; Yaakob, Mohd Aizul (STAI Auliaurrasyidin Tembilahan, 2025)
Islamic Religious Education (PAI) aims to translate religious knowledge into consistent practice, with prayer (salat) as a key outcome. However, a significant value-action gap often persists. This study investigated the mechanisms through which PAI learning influences Dhuhr prayer performance among Grade VII students at SMP Negeri 4 Rengat, Indonesia. A sequential explanatory mixed-methods design was employed, framing the analysis through the Theory of Planned Behavior (TPB). Quantitative data from all 52 students revealed that while the direct effect of PAI learning on prayer was weak, a model incorporating TPB constructs was highly significant, explaining 51.2% of the variance. Perceived Behavioral Control (PBC) was the strongest predictor (β = .59, p < .001), followed by Subjective Norms. Attitude was not a significant unique predictor. Qualitative interviews and observations with a sub-sample clarified that PBC was undermined by practical barriers like lack of confidence in prayer movements and social distractions, while norms operated through peer influence. The findings demonstrate that the PAI-prayer relationship is not direct but is critically mediated by students' perceived control and social environment. This necessitates a pedagogical shift beyond knowledge delivery towards interventions that build practical competency, scaffold habit formation, and cultivate supportive peer networks to bridge the gap between religious learning and lived practice.